Area deprivation is inversely associated with measles incidence: A spatiotemporal analysis in Germany. (30th September 2020) - Rohleder, S; Stock, C; Bozorgmehr, K
Abstract: Background: Although measles is endemic in all WHO European regions, very few studies have directly analysed socioeconomic inequalities in disease incidence of measles. We examined the spatiotemporal association between socioeconomic deprivation and measles incidence considering relevant demographic and geographical factors at district level. Methods: We conducted a longitudinal small-area analysis using nationally representative data of 401 districts from 2001 to 2017. We used Bayesian spatiotemporal regression models to assess the potential effects of area deprivation on measles incidence, adjusted for relevant demographic (district population size, sex, age, and proportion of non-nationals) and geographical factors (north-south-west-east effect) as well as spatial and temporal effects. We computed risk ratios (RR) for deprivation quintiles (Q1 - Q5), and district-specific adjusted relative risks (ARR) to assess the area-level risk profile of measles in Germany. Results: The risk of measles infection in areas with lowest deprivation quintile (Q1) was 1.58 times higher (95%-credible interval [CrI] 1.32-2.00) than in those with highest deprivation (Q5). Areas with medium-low (Q2), medium (Q3), and medium-high deprivation (Q4) had higher adjusted risks of measles relative to areas with highest deprivation (Q5) (RR: 1.23 (0.99-1.51), 1.05 (0.87-1.26), and 1.23 (1.05-1.43), respectively). We identified 22 areas at high risk and 56 at medium-high risk for measles infections, with highest area-level risks in south-western Germany. Conclusions: Socioeconomic deprivation in Germany is inversely associated with measles incidence, with elevated risk for measles infections in areas with higher socioeconomic status. Our findings contribute to current global and national debates on measles elimination strategies, and demonstrate the importance of spatial modelling techniques in identifying socioeconomic inequalities and spatial risk patterns of measles for public health actions. Key messages: Socioeconomic deprivation is inversely associated with measles incidence in Germany, with higher risk of infection in areas with highest socioeconomic status. The social, spatial, and temporal patterns of elevated risk of measles infection require targeted public health action and policy to address the complexity underlying measles epidemiology.